(3eSfO GdeQhRis - (3GdeQhRj , eMeO Hf fUQ GdeQhRj, CHh YHO Gddg,J (B294 (3g` s
(3ChdgG (B:s
(3JHJOF HHGH ai JYXje bOQ GdUdGII s
(3BNQgG (B:s
(3hjfJgi HPcQ GdCNHGQ GdJi LGAJ ai Cf SHGH GdeSde aShb s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B125 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B87s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B102 s
Keywords: (3GdMOjK h GdeUWdMs